Browne, Kath i Ferreira, Eduarda (2015). Lesbian Geographies: Gender, Place and Power - Soler Rodríguez, Laura (Documents d’Anàlisi Geogràfica, 2019)
Browne, Kath i Ferreira, Eduarda (2015) Lesbian Geographies: Gender, Place and Power Londres: Routledge, 286 p. ISBN 978-1472443950